1998
DOI: 10.1080/10220119.1998.9647936
|View full text |Cite
|
Sign up to set email alerts
|

Modification of soil nutrients and micro‐climate by tree crowns in a semi‐arid rangeland of south‐western Zimbabwe

Abstract: Tree crowns in semi-arid areas have often been found to create micro-habitats of improved soil physical and nutrient status and reduced evapotranspiration. These encourage the growth of mesic, palatable and high yielding perennial grasses in otherwise arid environments. A two-year study, in areas with a long history of light grazing, at Matopos Research Station sought to establish whether the soil nutrient status and micro-climate under tree crowns are different from those in open areas, and whether the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…First and foremost, inputs of organic matter to the soil are reduced by burning because of the combustion of aboveground biomass and leaf litter. Secondly, the removal of vegetation tends to increase the number of wetting and drying cycles in the soil surface, due to greater soil temperature (Savage and Vermeulen, 1983) and less interception of rainfall in the exposed post-fire environment (Moyo et al, 1998). This in turn increases the rate of mineralisation of organic matter, a process known as the Birch (1958) effect.…”
Section: Soil Crusting and Long-term Burningmentioning
confidence: 98%
“…First and foremost, inputs of organic matter to the soil are reduced by burning because of the combustion of aboveground biomass and leaf litter. Secondly, the removal of vegetation tends to increase the number of wetting and drying cycles in the soil surface, due to greater soil temperature (Savage and Vermeulen, 1983) and less interception of rainfall in the exposed post-fire environment (Moyo et al, 1998). This in turn increases the rate of mineralisation of organic matter, a process known as the Birch (1958) effect.…”
Section: Soil Crusting and Long-term Burningmentioning
confidence: 98%
“…The direct effect is a reduction in inputs of litter and root biomass. Indirectly, however, the effect of temperature (Du Preez & Snyman, 1993), wetting and drying cycles (Birch, 1958;Savage & Vermeulen, 1983;Du Preez & Snyman, 1993;Jordaan & Rautenbach, 1996;Moyo, Frost & Campbell, 1998), possible inhibitory effects of plant roots on microbial activity and the sometimes excessive removal of N relative to C (Theron, 1951) may all contribute to a decline in SOM when vegetation is removed. Theron (1951) showed that grass leys had a reduced rate of mineralisation relative to fallow soils, which he ascribed to the release of antibacterial exudates from grass roots.…”
Section: Understanding the Causes And Mechanisms Of Soil Degradationmentioning
confidence: 99%
“…Subsequent nutrient release from leaves, twigs and roots may have an important influence on the organic matter and nutrient budget of the soil (Szott et al, 1991;Young, 1989). Tree crowns in semi arid areas have often been found to create microhabitats of improved soil physical and nutrient status and reduced evapo-transpiration (Moyo et al, 1998). The presence of tree canopies increases soil organic carbon content, moisture availability and nutrient status (Anil et al, 1998).…”
Section: Introductionmentioning
confidence: 99%